Multipoint NIR spectroscopy for simultaneous analyses of dairy products – Part B: Quantification. Issue 5 (August 2017) - Cama-Moncunill, Raquel; Dixit, Yash; Cama-Moncunill, Xavier; Casado-Gavalda, Maria P; Markiewicz-Keszycka, Maria; Cullen, Patrick J; Sullivan, Carl
This article constitutes the second part of the study multipoint NIR spectroscopy for simultaneous analyses of dairy products. The overall purpose was to assess the suitability of a multipoint NIR approach as an on/in-line tool for simultaneous monitoring of various quality control parameters. In this part, a multipoint NIR system capable of recording 4 spectra concurrently was tested for simultaneous casein determinations of casein-lactose blends. To this end, spectral acquisition was performed so that two sample blends were scanned at a time. Evaluation of the concurrently-recorded spectra together with the partial least squares (PLS) results demonstrated that the system holds potential for simultaneous compositional analysis of dairy powders.